2020
DOI: 10.5222/jarss.2020.57441
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pleth Variability Index (PVI) to Evaluate Intraoperative Fluid Management During Orthopedic Spinal Surgery: A Randomized Controlled Trial

Abstract: Objective: To prevent complications during major surgery, it is important to monitor blood and fluid treatment. The Pleth Variability İndex (PVI) allows noninvasive assessment of fluid management. It is based on respiratory changes in arterial pulse pressure. In our study, we aimed to compare the management in terms of variations in PVI in response to fluid loading in the monitorization of intraoperative fluid management in major surgery using classical calculation method and CVP Method: The patients were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…In a prospective study conducted by Çevikkalp et al on 100 patients aged 18 and above undergoing elective posterior lumbar stabilization surgery with ASA I-II classification, they compared the classic calculation method and CVP monitoring for intraoperative fluid management with fluid loading based on PVI changes. This study indicates that the noninvasive nature of the PVI method and its ability to provide more accurate results in assessing the patient’s intravascular volume demonstrate the value of PVI as a valuable method during surgery [ 4 ]. When we review studies evaluating fluid responsiveness in patients in the prone position in the literature, Yang et al found that SVV and PPV values showed fluid responsiveness at lower threshold values in supine compared to patients who were placed in the prone position using a Wilson frame [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective study conducted by Çevikkalp et al on 100 patients aged 18 and above undergoing elective posterior lumbar stabilization surgery with ASA I-II classification, they compared the classic calculation method and CVP monitoring for intraoperative fluid management with fluid loading based on PVI changes. This study indicates that the noninvasive nature of the PVI method and its ability to provide more accurate results in assessing the patient’s intravascular volume demonstrate the value of PVI as a valuable method during surgery [ 4 ]. When we review studies evaluating fluid responsiveness in patients in the prone position in the literature, Yang et al found that SVV and PPV values showed fluid responsiveness at lower threshold values in supine compared to patients who were placed in the prone position using a Wilson frame [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Optimizing the intravascular volume status is very important to prevent postoperative organ failure and reduce complications [ 4 ]. When hemodynamic changes that may occur during anesthesia and surgery can be predicted in advance, unwanted hemodynamic effects are prevented.…”
Section: Introductionmentioning
confidence: 99%